Effects of mindfulness-based stress reduction and an organizational health intervention on Dutch teachers’ mental health - Janssen, Math; Heerkens, Yvonne; Van der Heijden, Beatrice; Korzilius, Hubert; Peters, Pascale; Engels, Josephine (Health promotion international, 2023)
Summary This study aimed to test the effectiveness of mindfulness-based stress reduction (MBSR) combined with an organizational health intervention. A cluster randomized controlled trial was conducted in five Dutch secondary vocational schools. Teachers were assigned to Intervention Group 1 (IG1; MBSR) or 2 (IG2; MBSR and an organizational health intervention), or to the Waiting List Group. The primary outcome variable was mindfulness. Secondary outcomes included other mental health outcomes, work performance, personal competencies, and work-related perceptions. Data was collected before (T0), immediately after (T1), and three (T2) and nine months (T3) after the MBSR training and analyzed applying repeated measures between-subjects designs. As the additional intervention showed no effects, IG1 and IG2 were merged (IG). MBSR had positive short-term effects on the total mindfulness score, its dimensions ‘observing’ and ‘non-reactivity’, and the work engagement dimension ‘dedication’. Long-term effects were found for the total mindfulness score, its dimensions ‘observing’, ‘non-reactivity’, and ‘non-judging’, sleep quality complaints, negative emotions, and negative work–home interaction. IG displayed a larger short- and long-term decrease in organizational commitment. No significant differences were found for work performance, personal competencies, and work-related perceptions. Although teachers did not perceive a decrease in job demands after the training, they felt more mindful and lowered their organizational commitment. Their mental health improved and their dedication during work increased. These findings may suggest that enhanced mindfulness enabled them to mentally disengage from work during their leisure time, which allowed them to experience fewer symptoms of psychological strain. The trail is registered with the Dutch Trial Register (www.trialregister.nl): NL5581 (July 2016).